2022
DOI: 10.14218/fim.2022.00010
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Spinal Stenosis: Considerations for Treatment

Abstract: Acupuncture has been a staple of Eastern medicine for thousands of years. Recent evidence has shown that the benefits for spinal stenosis are strong. In this comprehensive review, the history and available literature will be reviewed. In addition, how the techniques have evolved, and their clinical utility will be discussed. The process and progression of spinal stenosis are addressed. The mechanism of action for acupuncture and the relevant treatment implications will be discussed. This is important in allevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…21 In spinal stenosis, acupuncture was found to be effective in LSS treatment through biochemical mechanisms to induce analgesia and stimulate peripheral receptors of neurons. 22 ICT is a popular treatment that alleviates pain in patients with chronic back pain. According to the gate control theory, stimulation via ICT relieves chronic back pain by interfering with the transmission of nociceptive receptor information from the spinal dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…21 In spinal stenosis, acupuncture was found to be effective in LSS treatment through biochemical mechanisms to induce analgesia and stimulate peripheral receptors of neurons. 22 ICT is a popular treatment that alleviates pain in patients with chronic back pain. According to the gate control theory, stimulation via ICT relieves chronic back pain by interfering with the transmission of nociceptive receptor information from the spinal dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Various conservative therapies are used for LSS management; however, recent studies revealed that acupuncture has better analgesic effects than nonsteroidal anti-inflammatory drugs or physical therapy. 6 , 7 Pharmacopuncture therapy (PPT) is a combined technique that involves the infusion of medicinal extracts and acupuncture to achieve a synergistic effect. 8 , 9 In Korean clinical practice, PPT is selectively incorporated into conventional Korean Medicine treatment (CKMT), including acupuncture, electroacupuncture, and cupping for treating musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%